ENFORCEMENT OF SINTANG REGENCY REGIONAL REGULATION NUMBER 13 OF 2017 CONCERNING PUBLIC ORDER BY THE SINTANG REGENCY PAMONG PRAJA POLICE UNIT - Riyanto, Maria Angela; Dananjaya, Gede Bhayu (Jurnal Tatapamong, 2024)
Sintang Regency still faces problems in the context of public order, primarily related to alcoholic beverage business licenses. This study aims to describe and analyze the enforcement of Sintang Regency Regional Regulation Number 13 of 2017 concerning Public Order by the Sintang Regency Pamong Praja Police Unit, specifically regarding alcoholic beverage business licenses. The research method is descriptive-qualitative. The results showed that in carrying out the duties and functions of enforcing regional regulations, the Satpol PP of Sintang Regency faced problems related to the lack of public understanding of obtaining business licenses and also the Pamong Praja Police Unit, which did not provide sufficient understanding to the public regarding related regional regulations. In conclusion, the enforcement of Sintang Regency Regional Regulation Number 13 of 2017 concerning Public Order by the Sintang Regency Pamong Praja Police Unit is quite well implemented. It needs to be strengthened in several aspects, including by conducting intense socialization activities, strengthening leadership commitment, and employee participation in training activities relevant to duties and functions.